Antecedents of E-Loyalty as Research for the Quick Commerce Industry - Setiyono, Agus Eko; Chandrawatisma, Chodilis; Fanandi, Rizal Helga Sutan; Heriyati, Pantri (Interdisciplinary Social Studies, 2023)
Background: Quick Commerce is currently the third generation business model after conventional stores and e-commerce, currently very attractive and huge market potential. Aim: The purpose of this study is to analyze the impact of E-Service quality on  customer satisfaction and E-Loyalty of q-commerce customers in Indonesia. Method: The study was designed cross-sectionally  using a well-structured questionnaire so that holistic information could be obtained on 341 q-commerce customers in  Indonesia who often use  the platform in fulfilling their daily needs. The research instrument is validated, then the collected data is analyzed using Smart Partial Least Square (PLS) for hypothesis testing. Findings: The results revealed a statistically significant positive relationship between service quality and its dimensions (safety, reliability, convenience, responsiveness), customer loyalty, and customer satisfaction. This research contributes to the study of online shopping  on q-commerce platforms and provides advice over possible factors that may influence E-Service quality decisions.